A New Adaptive Anti-windup Controller for Wind Energy Conversion System Based on PMSG - Ed-dahmani Chafik; Mahmoudi Hassane; Bakouri Anass; El Azzaoui Marouane (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In this paper, an adaptive anti-windup control strategy for permanent magnet synchronous generator dedicated for wind energy conversion systems. The proposed control has the advantage to suppress the performance deterioration caused by the overshooting phenomenon, and optimize the controller gains using the particle swarm optimization algorithm. The scheme of the speed controller is implemented on ﬁeld orientation control in the generator side converter. A simulation of the proposed scheme is carried out in SIMULINK-MATLAB in order to evaluate the eﬀectiveness of the control against the saturation and the parameter optimization.